State Crime by Proxy and Juridical Othering - Jamieson, Ruth (The British journal of criminology, 2005)
This paper explores the range of strategies employed by states to obfuscate their responsibility in state crime through othering' both perpetrators and victims. It draws upon a range of frameworks of international humanitarian law, human rights, transitional justice as well as criminological theory to explore the historical and contemporary techniques of obfuscation. The first part of the article focuses upon the ways in which state agency is either exercised covertly or by proxy. Strategies include resort to perfidy', the expanded use of specialist' forces, collusion with indigenous paramilitaries and the use of private-sector mercenaries and military firms to outsource state deviance. The second part of the article then examines the othering' of the enemies of the state. These strategies include holding detainees outside national territories, using third-party nations to carry out torture or redefining the status of individuals to designate them as juridical others', with few national or international legal protections. The authors conclude that the notion of state crime should move beyond a monolithic conceptualization of the state and that a more subtle grasp of the different modalities of proxy agency and othering encourages us to look beyond retributive-centred international and national criminal law as but one of the mechanisms for attributing responsibility for state deviance